Simultaneous Spectophotometric Estimation of Moxifloxacin Hydrochloride and Vinblastin Sulphate - Pradhan, Nayan (International Journal of Pharmaceutical & Biological Archive, 2015)
Simultaneous Spectophotometric Estimation of Moxifloxacin Hydrochloride and Vinblastin Sulphate